Skill transfer, expertise and talent development: An ecological dynamics perspective - Seifert, L.; Papet, V.; Strafford, B. W.; Coughlan, E. K.; Davids, K. (Movement & Sport Sciences - Science & Motricité, 2018)
In this paper, we propose an ecological dynamics perspective on expertise and talent development, with a focus on the role of skill transfer. The ecological dynamics theoretical framework provides an integrated explanation for human behaviour in sport, predicated on a conceptualisation including constraints on dynamical systems, ecological psychology and a complex systems approach in neurobiology. Three main pillars are presented (i.e., individual-environment coupling as the smallest unit of analysis; adaptation of a complex dynamical system to interacting constraints; and the regulation of action with perception) in order to discuss the functional role of behavioural variability, the usefulness of perceptual-motor exploration and the importance of general and specific skill transfer in the development of talent and expertise in athletes. In addition, practical implications for coaches and instructors are discussed, notably regarding early diversification and unstructured play and activities in talent development programs, but also through variable practice and constraints manipulation.